EVALUATION OF LOSSES IN COTTON HARVEST AT DIFFERENT HARVESTER SPEEDS - Júnior, Adailton Nogueira da Silva; do Vale, Welington Gonzaga; Andrade, Valfran José Santos; Enes, Adilson Machado; Vale, Patricia Azevedo Castelo Branco; Machado, Thiago Martins (Seven Editora, 2024)
The losses generated during the harvest of agricultural products are common, being due to the most varied problems, among them the speed of movement of the harvester. Thus, the objective of this work was to diagnose the losses in the cotton harvest as a function of the harvester's travel speed, seeking to relate them to phenological factors directly linked to the operation and that can contribute to the improvement of the harvest quality. The data were analyzed through sampling and for their presentation, descriptive statistics were used, seeking measures of central tendency and the occurrence of variability to represent the results. By the simple random sampling technique, the confidence intervals for the mean were obtained. Two travel speeds were used, 5.0 and 6.6 km h-1. It was sought to evaluate, before the passage of the harvester, maximum productivity and the pre-harvest loss, manually collecting all the cotton from the sample area, and immediately after the passage of the harvester, the total loss was collected. It was observed that the pre-harvest loss of cotton is relatively low and close to the values found in the literature for the State of Mato Grosso. The average total loss found remained within the limit considered acceptable. DOI:https://doi.org/10.56238/sevened2024.029-015